Manajemen Aset Sebagai Wujud Implementasi Tata Kelola Desa dan Pengidentifikasian Aset Untuk Meningkatkan Pendapatan Asli Desa - Sara, I Made; Adi Kurniawan Saputra , Komang (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to examine asset management and asset identification on increasingvillage original income. The population in this study are villages throughout BadungBali Regency, totaling 46 villages, which is then carried out by saturated sampling,which is a sampling technique when all members of the population are used as samples.This is often done when the population is relatively small. The technique of collectingdata is a questionnaire, because this study has a survey research design. Analysis ofresearch data using multiple linear regression or ordinary least square. The resultsshowed that asset management and asset identification had a significant positive effecton increasing village original income. This indicates that there is a need for assetclassification to record the potentials in the village that can be developed to supportvillage development and improve the welfare of rural communities. Qualified assetmanagement will have an impact on the village's original income.